Diagnostic imaging in pregnancy: Making informed decisions. (September 2019) - Lowe, Sandra
The use of diagnostic imaging involving ionising radiation may be necessary in pregnancy and requires an assessment of the most appropriate and safest imaging modality which will provide the necessary information balanced with the potential risks to the mother and fetus. In most cases, this will involve a potential fetal radiation dose well below 50 mGy. At these doses, there is no risk of lethality, genetic damage/epigenetic change, teratogenicity, growth impairment or sterility. Older epidemiological data indicating a potential increased cancer risk have been contradicted by newer data and better understanding of the biology of low dose radiation. The linear no-threshold rule has been challenged by many and more realistic estimates of oncogenicity risk along with the potential risks of contrast agents are summarised in this review. Imaging in the pregnant population is increasing in both the number of examinations performed and the number of patients being imaged, with the greatest increase being computed tomography scans. Counselling and obtaining informed consent for imaging that involves radiation requires the clinician to communicate with the woman and her family a realistic estimate of the potential radiation dose to herself and her fetus, to describe and quantitate the risks of this estimated dose, to outline the benefits of the imaging procedure and to respond to any questions or concerns. As almost all diagnostic imaging involves doses below the 50 mGy threshold, clinically indicated investigations should not be withheld during pregnancy. All allied staff must also be well informed to ensure the patient receives a consistent message about the risks and benefits of the proposed test.